Push and pull factors and development strategy of tea smallholder agroindustry in case study Barokah Farmer Group Ciwidey - Siti Utami Tammah (Jurnal Penelitian Teh dan Kina, 2017)
Tea plant with the Latin name Camellia sinensis is one of the plantation commodities suitable for cultivation in Indonesia. Indonesia is the seventh country as a tea producer in 2016. The tea plantation area in Indonesia is still dominated by smallholder tea estate of 45.17%. This study aims to identify (1) pull factors and push factors of tea smallholder agro industry at Barokah Farmer Group in Lebak Muncang Village Ciwidey Subdistrict, Regency of Bandung, (2) to formulate alternative strategy and to determine strategic priority that can be applied. The technique used in this research is case study. Informants in this study were determined purposively. The result of research shows that there are pushing and pulling factors on the tea agroindustry of Tani Barokah group such as good product quality, good raw material continuity, solid worker with family sense, customer loyalty, suitable area for tea business Plantation and activities for promotion which organized by government agency of Bandung Plantation Office. Alternative strategies that can be applied based on existing internal and external factors are: Increasing the intensity of work by intensifying, selling online, preparing and setting Standard Operating Procedure (SOP), expanding marketing network by partnering with retail or distributors, cooperating with experts to assist optimize the yield of raw materials, shoots, and cooperating with tea bag industry.